Penatalaksanaan Rheumatoid Arthritis Pada Petani Wanita Usia Lanjut Melalui Pendekatan Kedokteran Keluarga - Nailul Azizah; Reni Zuraida (CV. Jasa Sukses Abadi, 2020)
Rheumatoid Arthritis (RA) is an autoimmune disease characterized by erosive, symmetrical synovitis and requires long-term treatment so family support is needed in its management. This study is a case report. Primary data obtained through history taking, physical examination, and home visits. Secondary data were obtained from the patient's medical record. At the first visit, the patient's complaint was pain in the proximal interphalangeal joint (PIP) digital I-V dextra et sinistiti. Internal risk factors namely lack of knowledge about the causes of RA, precipitating factors, how to deal with acute symptoms, diet and exercise are recommended. External risk factors in patients are families who pay less attention to diet and exercise recommended to patients and do not use shoes and waterproof gloves and do repetitive movements without resting when farming. The second visit was to be intervened with the family conference method using poster media. The third visit found complaints of reduced joint pain because the patient took piroxicam 10 mg and applied liniment to the painful location. Patients have been consuming fruit and milk regularly and exercising muscle stretches three times a week for 30 minutes. Families remind diet and exercise accordingly. When farming use shoes and waterproof gloves and rest between repetitive movements. There is an increase in patient knowledge about the causes, precipitating factors, how to deal with acute symptoms, diet, and exercise that is appropriate for RA, characterized by an increase in post-test scores of 40.